MENINGKATKAN KETERAMPILAN MOTORIK KASAR MELALUI SENAM IRAMA BINATANG - Dedeh Ubaedah; Atin Fatimah; Ratih Kusumawardani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
The gross motoric skills of children in PAUD Darul Ula Curug Kota Serang are still low, so they experience obstacles to body balance, coordination of limbs, flexibility of limbs and strength of limbs, this is caused by lack of variation in classroom learning strategies. The learning process becomes monotonous and boring for children. It is hoped that rhythmic gymnastics can improve the gross motor skills of children aged 5-6 years. In this study aims to improve the skills of children in gross motor aspects in Darul Ula Curug PAUD, Serang City. This type of research is classroom action research (CAR). This study consisted of two cycles, each cycle consisting of 8 meetings in the first cycle and 2 meetings in the second cycle. The subjects of this study were children from the B PAUD Darul Ula group with a total of 10 children, 7 boys and 3 girls. The technique of collecting data through observation, interviews and documentation. The instrument used is the observation sheet. The analysis was carried out descriptively qualitatively and quantitatively, with the success criteria of action, the average percentage of 70% of children experienced gross motor improvement. The process of applying animal rhythmic exercises uses several stages of research, namely, planning, implementation and action, and reflection. The results of this study note that, in the initial assessment of children’s gross motor skills 37%, after being given the first action cycle, the gross motor skills of children increased to 56%, and in the second cycle the results were 83%. So it can be concluded that through animal rhythmic activities, it can improve the gross motor skills of children aged 5-6 years in PAUD Darul Ula Curug Kota Serang.